"Acoustic-driven oscillators as cortical pacemaker": a commentary on Meyer, Sun & Martin (2019). Issue 9 (3rd November 2020) - Ghitza, Oded
ABSTRACT: This is a commentary on a review article by Meyer, Sun & Martin (2019), "Synchronous, but not entrained: exogenous and endogenous cortical rhythms of speech and language processing", doi:10.1080/23273798.2019.1693050 . At the heart of this review article is the language comprehension process. Anchored at a psycho- and neurolinguistic viewpoint, the article argues for the centrality of endogenous cortical rhythms, not only as the facilitators of processes that generate abstract representations and predictions of language but also of processes that establish intrinsic synchronicity with the acoustics, with the priority to override processes realized by acoustic-driven, exogenous cortical rhythms. In this commentary I propose that the scaffold for the speech decoding process – through parsing – is an acoustic determinant. Whether oscillation driven or not, the decoding process is paced by a hierarchical cortical clock, realized by oscillators locked to the input rhythm in multiple Newtonian-time scales, keeping the decoding process in sync with the linguistic information flow. Only if such a lockstep is secured can reliable decoding proceed.